2019
DOI: 10.1590/1806-9282.65.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different types of endovascular mechanical embolectomy in acute ischemic stroke

Abstract: SUMMARY Background: To compare the treatment efficacy of different types of endovascular mechanical embolectomy in acute ischemic stroke (AIS). Material and Methods: A total of 89 patients with AIS were selected in our hospital from January 2014 to January 2016 and divided into tPA group (n=27), tPA+Trevo group (n=30) and tPA+Solitaire FR group (n=32) for different treatments. Treatment effectiveness was evaluated using NIHSS and mRS system. The NIHSS score, vascular recanalization rate and postoperative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In addition, mechanical thrombectomy could enhance thrombolytic therapy. Studies have confirmed that combining mechanical thrombectomy and thrombolytic drugs achieves superior efficacy and safety than thrombolytic drugs alone [44] .…”
Section: Overview Of Ismentioning
confidence: 99%
“…In addition, mechanical thrombectomy could enhance thrombolytic therapy. Studies have confirmed that combining mechanical thrombectomy and thrombolytic drugs achieves superior efficacy and safety than thrombolytic drugs alone [44] .…”
Section: Overview Of Ismentioning
confidence: 99%
“…The principle of treatment is to restore the blood flow of the ischemic tissue as soon as possible, deliver nutrients such as sugar and oxygen, and reduce ischemia-reperfusion injury and cell apoptosis. 2 Leptin is a polypeptide hormone encoded by an obesity (OB) gene with a molecular weight of 16 kDa. Leptin is mainly synthesized and released by fat cells.…”
Section: Introductionmentioning
confidence: 99%